The Effect Of Affiliate Credibility And Tiktok Video Content Quality On Purchase Decisions Among Generation Z In Bengkulu City - Septi Septi; Karona Cahya Susena; Yanto Effendi (Utami Publisher, 2025)
The development of social commerce through TikTok with an affiliate marketing system has changed the shopping behavior of Generation Z, particularly in the purchasing decision-making process. Product promotion success is not only determined by price and brand, but also by affiliate credibility and the quality of video content presented. This study aims to analyze the effect of affiliate credibility and TikTok video content quality on purchasing decisions of Generation Z in Bengkulu City. This research used a quantitative descriptive method with purposive sampling technique involving 70 respondents. Data were collected using questionnaires with a five-point Likert scale and analyzed using SPSS version 23 through validity tests, reliability tests, multiple linier regression analysis, t-tests, F-tests, and coefficient of determination analysis. The results show that affiliate credibility and video content quality have a positive and significant effect on purchasing decisions, both partially and simultaneously. The coefficient of determination value of 0.352 indicates that the two independent variables explain 35.2% of the variation in purchasing decisions. These findings indicate that higher affiliate credibility and better video content quality increase the likelihood of Generation Z making purchases through TikTok.